Analisis kesulitan mahasiswa bimbingan dan konseling dalam melaksanakan Praktik Pengalaman Lapangan (PPL) - Saleha Saleha; M. Husen; Abu Bakar (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2019)
Abstract: This research is entitled "Analysis of Difficulties of Guidance and Counseling Internship Students in Implementing the Internship Program ". The purpose of this study was to determine the difficulties of guidance and counseling students in carrying out the practice of field experiencein internship program. The research method is a descriptive method with a qualitative approach. The research subjects were internship students from the Counseling Guidance Department who implemented the 2015/2016 internship program. The research data was obtained from students through the interview. Data analysis techniques are carried out by data reduction, data presentation and data verification. The results of this study indicate that, some students have difficulty in making syllabus, compiling annual, semester, and daily programs, some students are able to develop material, only using media and learning resources that are suitable to be applied to students, in preparing student lesson plans difficulties as well as in the implementation of learning activities and assessment of learning outcomes or evaluating student learning outcomes, feeling inadequate in setting materials and learning objectives as well as in selecting and organizing materials, media, and student learning resources, difficulties in managing routine tasks, learning facilities, and time, classroom management, as well as the use of learning strategies and in using language and behavior, as well as being less able to foster positive attitudes of studentsKeywords: Student difficulties, internship program Abstrak: Penelitian ini berjudul “Analisis Kesulitan Mahasiswa Bimbingan dan Konseling dalam Melaksanakan Praktik Pengalaman Lapangan”. Tujuan penelitian ini untuk mengetahui kesulitan mahasiswa bimbingan dan koseling dalam melaksanakan praktik pengalaman lapangan. Metode penelitian adalah metode deskriptif dengan pendekatan kualitatif. Subyek penelitian adalah Mahasiswa PPL Jurusan Bimbingan Konseling yang melaksankan PPL tahun 2015/2016. Data penelitian ini diperoleh dari mahasiswa melalui wawacara. Teknik analisis data dilakukan dengan reduksi data, penyajian data dan verifikasi data. Hasil penelitian menunjukan bahwa, sebagian mahasiswa kesulitan dalam membuat silabus, menyusun program tahunan, semesteran, dan harian, beberapa dari mahasiswa mampu dalam mengembangkan materi, hanya saja kurang menggunakan media dan sumber belajar yang cocok untuk diterapkan kepada siswa, dalam penyusunan RPP mahasiswa merasa kesulitan begitu juga dalam pelaksanaan kegiatan pembelajaran dan penilaian hasil belajar atau mengevaluasikan hasil belajar siswa, merasa kurang mampu dalam menetapkan bahan dan tujuan pembelajaran begitu juga dalam memilih dan mengorganisasi materi, media, dan sumber belajar siswa, kesulitan dalam pengelolaan tugas rutin, fasilitas belajar, dan waktu, pengeloaan kelas, begitu juga dalam penggunaan strategi pembelajaran dan dalam menggunakan bahasa dan perilaku, serta kurang mampu dalam menumbuhkan sikap positif pada siswa.Kata kunci: Kesulitan mahasiswa BK-Praktik Pengalaman Lapangan (PPL)